Comparing the Normal Range and Changes Process of Lumbar Curve in Male and Female Students Aged 10 to 18 Years - Morteza Sadeghi; Gholamali Ghasemi (Shiraz University of Medical Sciences, 2017)
Background: In recent years, several studies on the body posture have been done at schools, most of which have shown a high prevalence of varying abnormality among students. The aim of this study was to investigate the normal range and changes process of lumbar curve in students, both girls and boys, in the age group of 10 to 18 years. Methods: A total number of 1800 students (male and female), in the age group of 10 to 18 years were selected to participate in the present study. The student samples were chosen from the different cities of the Isfahan province in a randomized and clustered manner. Each age category included 100 male and female students each. The flexible ruler was used to measure the lumbar curve angle. The factorial ANOVA method, in SPPS16, was used for data analysis with α=0.05. Results: The data analysis showed that the age changes factor and gender factor have a significant effect on lumbar curve changes in the level of P<0.05. However, the interaction between gender and age was not significant (P>0.05). This means that the changes process is similar in both gender groups. Conclusion: The lumbar curve angle is generally higher in girls. Moreover, this angle increases in both genders as age increases to 18 years. The extent of the lumbar curve exceeds the normal limit in girls after 13 years of age with the onset of puberty, which means that girls in this age group need additional attention from the concerned authorities in order to prevent spinal abnormalities.